REFLEXÕES ACERCA DA FORMAÇÃO E PERCEPÇÕES DISCENTES EM CONTEXTOS DIVERSOS - ANA PAULA LEÃO MENDES (2021)
ABSTRACT The objective of this study was to explain, discuss and analyze the perceptions and representations of students from the Law, History and medicine undergraduate courses at the Federal University of Mato Grosso do Sul, Três Lagoas-MS, about race, class and gender relations. The choice of research subjects is due to the fact that they are in a formative process immersed in a capitalist social structure, the university, which in turn can also be seen as a space that reproduces social inequalities. Is the academic environment a space for social formation or exclusively for intellectual formation? We will take as references studies in the field of sociology to think about the issue of childhoods; in the field of anthropology, History and philosophy to understand ethnic and "racial" issues, and studies in the field of education as the focal point of the interrelation of objective and subjective formation processes; references of feminist studies to analyze the issue of gender Therefore, this is a qualitative research that appropriates the methodological tools and techniques of the ethnographic procedure (field notebook and questionnaires) intertwined with document analysis from previously selected references. Thus, aiming to analyze densely the perceptions of the students of the aforementioned courses before the social demands listed in this study. Our conclusions indicate a student profile that shows itself as belonging to a wealthier social class, besides signaling an absence of minorities in this space of high-level knowledge production. Keywords: Students from CPTL/UFMS. Formation/Education. Social relations.